Analisis Kadar Serat dan Uji Daya Terima Sereal Substitusi Tepung Singkong dan Kacang Merah - Nevi Yoga Sulistyowati; Tri Yunita Fitriya Damayanti; Ahmad David Royyifi (Media Gizi Ilmiah Indonesia, 2025)
In general, cereals on the market are made from wheat flour, which contains quite a high sugar content and is low in fiber, so it is necessary to modify cereal recipes to increase nutritional value. Cassava flour is a food source of carbohydrates and contains higher fiber than wheat flour. Red bean flour has a relatively high protein content and low glycemic index, so that the substitution of cassava flour and red bean flour is expected to increase the fiber content.This study aims to determine the effect of substitution of cassava flour and red bean flour on the nutritional value and acceptability test of cereals.This study used True Experimental Completely Randomized Design, 4 levels of treatment and 6 times of replication. The treatment applied was the ratio of wheat flour: cassava flour: red bean flour at each P0 (100:0:0), P1 (10:50:40), P2 (10:60:30), P3 (10: 70:20).Based on the results of the study, it was shown that there was an effect of increasing fiber content in cereals, with the highest fiber content in treatment P1. Furthermore, there is a significant effect on color and texture (Kruskall-Wallis (p<0.005) and no significant effect on taste and aroma (Kruskall-Wallis (p>0.005).Cereals substituted for cassava flour and red bean flour have an effect on fiber content and acceptability test.